Desıgning a Secure Blockchain-Based Trading Platform for Internet of Things - Osmanoğlu, Murat; Elbuz, Aydın; Tanrıöver, Ömer Özgür (Ankara Üniversitesi Fen Fakültesi, 2019)
Blockchain, a distributed database technology attracts intensive attention recently. It was first described in 1991 by Stuart Haber and W. Scott Stornetta, in order to prevent tampering for document timestamps. After that, Satoshi Nakamoto conceptualized this technology with his work, a peer-to-peer electronic cash system named as Bitcoin. Due to its authenticity, user anonymity and data immutability; this technology has also been applied to different areas ranging from finance, supply-chain managements to social services. In this paper, we propose a blockchain based application for trading data, collected from IoT devices. Our application enables the sellers to commercialize their data in exchange of the currency produced by the application. The application also utilizes smart contracts to establish trust between both sides of the exchange. Furthermore, we discuss the security and reliability of the system components
Keywords: Blockchain; Internet of things; Distributed ledger